2021
DOI: 10.1186/s12902-021-00684-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between diabetes and thyroid cancer risk: a hospital-based case-control study in China

Abstract: Background Previous studies have indicated inconsistent relationships of diabetes with thyroid cancer risk, yet little is known in China. In this study, we aimed to investigate the associations between diabetes, diabetes duration and the risk of thyroid cancer in Chinese population. Methods A 1:1 matched case-control study was performed between 2015 and 2017 in Zhejiang Province including 2,937 thyroid cancer cases and 2,937 healthy controls. Odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…Most of our included studies reported that DM increases the risk of cancer development; however, two studies reported that DM was associated with a lower risk of prostate cancer [14,22]. Some studies reported that the incidence of lung cancer [13], thyroid cancer [21], and bladder cancer [17] was not associated with DM.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 91%
See 4 more Smart Citations
“…Most of our included studies reported that DM increases the risk of cancer development; however, two studies reported that DM was associated with a lower risk of prostate cancer [14,22]. Some studies reported that the incidence of lung cancer [13], thyroid cancer [21], and bladder cancer [17] was not associated with DM.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 91%
“…A total of 15 studies were included in this review, with 1,080,106 diabetic patients who developed different types of cancers. Seven studies were conducted in the USA [13][14][15][16][17][18][19], two in China [20,21], one in Canada [22], one in the Australia [23], one in Lithuania [24], one in Poland [25] one in Finland [26] and one in the UK [27]. Regarding the studies' designs; Eight studies were retrospective in nature [13,16,19,20,22,[24][25][26], four were prospective [14,17,23,27], and two were case-control studies [15,21].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations